Nutraceutical regulation of miRNAs involved in neurodegenerative diseases and brain cancers. Issue 6 (June 2021) - Ghosh, Souvik; Kumar, Viney; Mukherjee, Haimanti; Lahiri, Debrupa; Roy, Partha
Abstract: The human brain is a well-connected, intricate network of neurons and supporting glial cells. Neurodegenerative diseases arise as a consequence of extensive loss of neuronal cells leading to disruption of their natural structure and function. On the contrary, rapid proliferation and growth of glial as well as neuronal cells account for the occurrence of malignancy in brain. In both cases, the molecular microenvironment holds pivotal importance in the progression of the disease. MicroRNAs (miRNA) are one of the major components of the molecular microenvironment. miRNAs are small, noncoding RNAs that control gene expression post-transcriptionally. As compared to other tissues, the brain expresses a substantially high number of miRNAs. In the early stage of neurodegeneration, miRNA expression upregulates, while in oncogenesis, miRNA expression is gradually lost. Neurodegeneration and brain cancer is presumed to be under the influence of identical pathways of cell proliferation, differentiation and cell death which are tightly regulated by miRNAs. It has been confirmed experimentally that miRNA expression can be regulated by nutraceuticals - macronutrients, micronutrients or natural products derived from food; thereby making dietary supplements immensely significant for targeting miRNAs having altered expression patterns during neurodegeneration or oncogenesis. In this review, we will discuss in detail, about the common miRNAs involved in brain cancers and neurodegenerative diseases along with the comprehensive list of miRNAs involved separately in both pathological conditions. We will also discuss the role of nutraceuticals in the regulation of those miRNAs which are involved in both of these pathological conditions. Abstract : Brain cancer, Neurodegenerative disease, miRNA, Nutraceuticals, Dietary supplements, , miR-9, miR-34abc, miR-29, miR-124, Let-7, miR-128, Apigenin, Luteolin, Resveratrol